Impact of therapeutic drug level monitoring on outcomes of patients with Crohn's disease treated with Infliximab: real world data from a retrospective single centre cohort study. Issue 4 (1st February 2019) - Kamperidis, Nikolaos; Middleton, Paul; Tyrrell, Tracey; Stasinos, Ioannis; Arebi, Naila
Abstract : Background: Therapeutic drug monitoring (TDM) by measuring infliximab (IFX) trough levels and antibodies to infliximab (ATI) is used to optimise treatment in inflammatory bowel disease. We aimed to explore the clinical outcomes of TDM for patients with Crohn's disease on IFX in real life setting. Methods: This is a retrospective observational study. Primary outcomes were the clinicians' response to each TDM result and the rate of IFX discontinuation due to secondary loss of response or serious adverse event. Secondary outcomes included the intestinal surgery rate after IFX initiation and remission 6 months after TDM. Multivariate logistic regression was performed to identify factors associated with IFX discontinuation and abdominal surgery. Results: 291 patients were included. 238 (81.8%) patients were tested for TDM at least once during their follow-up with 672 TDM results. 95/238 patients (39.9%) had undetectable levels and 76 (31.9%) had positive ATI at least once. The median infliximab trough level was 3.4 µg/mL. IFX was discontinued in 109 patients (37.5%). 526/672 (78.3%) TDMs results were not followed by altered patient management. Treatment was discontinued in 40 (75.5%) patients never tested for TDM compared with 69 (29.0%) of those tested (p<0.01). Fewer TDM tested patients (29; 12.2%) required intestinal surgery post IFX initiation compared with TDM not-tested (15; 28.3%). Not being TDM tested was independently associated with IFX discontinuation and abdominal surgery. Conclusions: IFX discontinuation and intestinal surgery were significantly less frequent with TDM. TDM requested to investigate loss of response resulted in change in patient management.